Integration of Local Wisdom in the Role of Village Heads as Mediators of Industrial Relations Disputes - Sarah Magfirah Daud; Nur Mohamad Kasim; Weny Almoravid Dungga (International Journal of Sociology and Law, 2024)
The integration of local wisdom in the role of village heads as mediators of industrial relations disputes is an effective strategy in rural conflict resolution. Local wisdom, which is a community's traditional knowledge and practices, can be used to understand and resolve complex conflicts. The village head, as a respected figure with traditional knowledge, can serve as an effective mediator in resolving industrial relations disputes. The results show that village heads play an important role as mediators by integrating local wisdom principles such as deliberation, mutual cooperation, and harmony in the mediation process. The custom-based approach proved effective in reaching an agreement that was acceptable to both parties and maintaining social harmony in the village. However, challenges arise when dealing with large companies or disputes involving formal legal aspects. This research provides new insights into the potential integration of local wisdom in the resolution of industrial relations disputes at the village level, as well as the implications for the development of a more contextualized alternative dispute resolution system in Indonesia. The analysis will discuss how the integration of local wisdom in the role of the village head can improve the effectiveness of conflict resolution in rural areas.